2019
DOI: 10.1165/rcmb.2018-0335oc
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Oxidation Protects against Hyperoxia-induced Endothelial Cell Apoptosis and Lung Injury in Neonatal Mice

Abstract: In neonates, hyperoxia or positive pressure ventilation causes continued lung injury characterized by simplified vascularization and alveolarization, which are the hallmarks of bronchopulmonary dysplasia. Although endothelial cells (ECs) have metabolic flexibility to maintain cell function under stress, it is unknown whether hyperoxia causes metabolic dysregulation in ECs, leading to lung injury. We hypothesized that hyperoxia alters EC metabolism, which causes EC dysfunction and lung injury. To test this hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
73
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 47 publications
9
73
0
3
Order By: Relevance
“…In agreement with our findings, neonatal hyperoxia for four weeks augments sphingomyelin species (SM16:0, SM18:0, SM24:0, and SM24:1), long chain ceramides (Cer16:0 and Cer18:0), and very long chain ceramides (Cer24:0 and Cer24:1) in bronchoalveolar lavage fluid from mice [ 28 ], and ceramide is increased in tracheal aspirates of preterm infants [ 9 ]. This may result in increased apoptosis with neonatal exposure to hyperoxia [ 2 , 29 ], despite there being no lung inflammatory responses observed in our 3-day hyperoxia-exposed mice (data not shown). Increased ceramide may be due to either increased hydrolysis of sphingomyelin or de novo synthesis in response to hyperoxic exposure [ 2 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In agreement with our findings, neonatal hyperoxia for four weeks augments sphingomyelin species (SM16:0, SM18:0, SM24:0, and SM24:1), long chain ceramides (Cer16:0 and Cer18:0), and very long chain ceramides (Cer24:0 and Cer24:1) in bronchoalveolar lavage fluid from mice [ 28 ], and ceramide is increased in tracheal aspirates of preterm infants [ 9 ]. This may result in increased apoptosis with neonatal exposure to hyperoxia [ 2 , 29 ], despite there being no lung inflammatory responses observed in our 3-day hyperoxia-exposed mice (data not shown). Increased ceramide may be due to either increased hydrolysis of sphingomyelin or de novo synthesis in response to hyperoxic exposure [ 2 ].…”
Section: Discussionmentioning
confidence: 93%
“…This may result in increased apoptosis with neonatal exposure to hyperoxia [ 2 , 29 ], despite there being no lung inflammatory responses observed in our 3-day hyperoxia-exposed mice (data not shown). Increased ceramide may be due to either increased hydrolysis of sphingomyelin or de novo synthesis in response to hyperoxic exposure [ 2 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Yao et al found that LC supplementation in endothelial cells accelerated FAO and attenuated apoptosis caused by hyperoxia. By using a CPT1 inhibitor (etomoxir, 100 μmol/L), they obtained the opposite result 39 . In addition, Gu et al suggested that full‐length CPT‐1a binds to endogenous bcl‐2, and this binding was critical in regulating apoptosis resistance of lung macrophages 26 .…”
Section: Discussionmentioning
confidence: 99%
“…After optimization, we seeded cells in Seahorse XF24 microplates (Seahorse Bioscience, Billerica, MA) overnight prior to the measurement of OCR. After optimization, we seeded human chondrocytes (60,000 cells/ well) in a Seahorse XF24 microplate (Seahorse Bioscience, Billerica, MA) overnight prior to the measurement of OCR as described earlier (Yao et al, 2019). The culture media were changed into the assay medium, which was the XF base medium supplemented with 1 mmol/L pyruvate, 2 mmol/L of glutamine, and 10 mmol/L glucose.…”
Section: Measurement Of Mitochondrial Oxidative Phosphorylationmentioning
confidence: 99%